Penguatan Rumah Jurnal di Pendidikan Tinggi - Sitti Nurfaidah; Mursalaat Mursalaat; Tomi Irawan Patra; Rani Chahyani (Institut Agama Islam Negeri Kendari, 2020)
The purpose of this research is to strengthen the management of rumah jurnal and the ability to manage scientific periodicals in managing e-journals in the scope of higher education, the availability of human resources in the field of sustainable e-journal management, the availability of articles ready for publishing in journals, which in ultimately leads the quality of e-journal publications meeting the standards of accreditation. Through an empowerment and development program, this research shows that there are several strategies carried out by rumah jurnal managers to empower the management capacity, i.e. improving the management of open journal system (OJS), increasing the capacity of e-journal managers, providing articles ready to be published, strengthening and improving the full circulation of OJS in the journal publishing process, and improving the journal so that it is ready for accreditation process.Keywords: Accreditation; empowerment; higher education; publication; rumah jurnal